Los intereses sectoriales de la vivienda social en Cuba - Adriana Rabinovich (EchoGéo)
In the first few years following the Cuban revolution, the State assumed full responsibility for public housing. The present contribution analyzes modalities for dealing with the tensions between technological and design-related criteria, as well as the role set aside for the public in collective housing policies and programmes since 1949. It sheds light on the statist model that has gradually given priority to quantity while defining quality via criteria for low-cost productivity. The example of the NGO Habitat-Cuba also illustrates the fragile nature of the innovative experiments of the 1990s, which attempted to reconcile technocratic aspects with the aesthetic, spatial and functional attributes of housing by means of so-called participatory approaches.